Prolidase activity in adult bipolar disorder patient: a case - control study - Joya, Joysree Das; Paul, Debatosh; Ahsan, Mohammad Shamsul; Bhuiyan, Mohammad Monzurul Alam; Rob, Rifat Mahbuba; Ferdousi, Sheuly; Islam, Md Saiful; Yesmin, Shaila (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Bipolar disorder is one of the major neuropsychiatric illnesses. It is responsible for 6.8% of disability-adjusted life years among all mental disorders. Few studies have evaluated the biochemical basis of bipolar disorder. Prolidase is an enzyme that degrade extracellular matrix into proline. In stress condition, prolidase by releasing proline maintain ATP generation, redox state, apoptosis and cell proliferation. The relationship between serum prolidase with bipolar disorder was investigated in this study. Method: A case - control study was conducted at the Department of Laboratory Medicine in collaboration with the Department of Psychiatry of Bangabandhu Sheikh Mujib Medical University, Dhaka from March 2021 to February 2022. Thirty-five patients with bipolar disorder type I consisting of 15 euthymic and 20 manic patients were enrolled in the study according to the availability of patients as cases. Thirty-five age - and sex-matched healthy individuals were recruited from the Department of Laboratory Medicine as controls. Serum prolidase level was measured in cases and controls using venous blood. Result: Serum prolidase level was significantly higher in cases than controls (P=0.021). There was no significant differences between euthymic and manic patients (P=0.629). Significant positive correlation was found between Young Mania Rating Scale severity score and serum prolidase level (P=0.001). Conclusion: Serum prolidase activity may be associated with bipolar disorder. This needs further corroboration because our sample size was small.